Impacts of HIV Cure Interventions on Viral Reservoirs in Tissues - Denton, Paul W.; Søgaard, Ole S.; Tolstrup, Martin (Frontiers in Microbiology, 2019)
HIV reservoirs persist in infected individuals despite combination antiretroviral therapy and can be identified in secondary lymphoid tissues, in intestinal tissues, in the central nervous system as well as in blood. Clinical trials have begun to explore effects of small molecule interventions to perturb the latent viral infection, but only limited information is available regarding the impacts of HIV cure-related clinical interventions on viral reservoirs found in tissues. Of the fourteen HIV cure-related clinical trials since 2012 that have evaluated the effects of small molecule interventions in vivo, four trials have examined the impacts of the interventions in peripheral blood as well as other tissues that harbor persistent HIV. The additional tissues examined include cerebral spinal fluid, intestines and lymph nodes. We provide a comparison contrast analyses of the data across anatomical compartments tested in these studies to reveal where peripheral blood analyses reflect outcomes in other tissues as well as where the data reveal differences between tissue outcomes. We also summarize the current knowledge on these topics and highlight key open questions that need to be addressed experimentally to move the HIV cure research field closer to the development of an intervention strategy capable of eliciting long-term antiretroviral free remission of HIV disease.